A critical multimodal analysis of the Romanian press coverage of camp evictions and deportations of the Roma migrants from France. Issue 4 (August 2018) - Breazu, Petre; Machin, David
In this article, we carry out a Multimodal Critical Discourse Analysis (MCDA) of a sample from a larger corpus of Romanian news articles that covered the controversial camp evictions and repatriation of Romanian Roma migrants from France that began in 2010 and continue to the time of writing in 2017. These French government policies have been highly criticized both within France and by international political and aid organizations. However, the analysis shows how these brutal, anti-humanitarian events became recontextualized in the Romanian Press to represent the French government's actions as peaceful and consensual. In addition, the demonization of the Roma in the press serves as a strategy to continuously disassociate them from their Romanian counterparts. While there is a long history of discrimination against the Roma in Romania, these particular recontextualizations can be understood in the context of the Romanian government's need to gloss over its failure to comply with the Schengen accession requirements and acquire full European Union (EU) membership.